Macrophage-targeted PEGylated liposomes ameliorate experimental autoimmune encephalomyelitis - Muselman, Alexander; Yu, Lewis W.; Nguyen, Khoa D.; Inayathullah, Mohammed; Liu, Qiang; Brewer, Kyle D.; Malkovskiy, Andrey V.; Rajadas, Jayakumar; Engleman, Edgar G. (Frontiers in Immunology, 2026)
Macrophages are the predominant immune cell type found in active multiple sclerosis (MS) and experimental autoimmune encephalomyelitis (EAE) lesions, where they contribute to demyelination and axonal damage. Depending on the lesion stage, these cells can exhibit either a pro-inflammatory or neurotoxic phenotype that drives central nervous system (CNS) injury or an anti-inflammatory phenotype that promotes remyelination. Therefore, strategies that modulate macrophage function may offer therapeutic benefits for MS. Polyethylene glycol (PEG) has shown anti-inflammatory and neuroprotective effects in various models of inflammation and neurodegeneration, but the mechanisms involved remain poorly understood. In this study, we investigated the potential of PEG and PEG-based delivery systems to modulate EAE. Although PEG alone did not alter EAE progression, it suppressed the pro-inflammatory phenotype of macrophages in vitro. Given the clinical potential and macrophage-targeting properties of larger PEGylated liposomes, we assessed the impact of large (~700 nm) PEGylated liposomes in EAE. These liposomes selectively targeted activated, CNS-infiltrating macrophages and, when administered to mice either before or after neurological manifestations of EAE had developed, they significantly reduced both clinical signs as well as demyelination in the spinal cord. Mechanistically, this treatment reduced macrophage secretion of pro-inflammatory cytokine IL-1β and decreased macrophage and T cell infiltration into the CNS compared to untreated controls. Together, these findings highlight the therapeutic potential of macrophage-targeted PEGylated liposomes in controlling IL-1β-mediated neuroinflammation in MS and potentially other neurodegenerative diseases.